Man and Alienation of Society - Subatavičiūtė, Angelė (Problemos, 1989)
Marxist theory constrains the essence of man to social relations. From the viewpoint of an individual the relation between man and society can be characterized by the concept of alienation. The alienation manifests itself as social (economic, political, ideological) forces, alien to the personal life of individual and presents by itself the result of labour alienation. However, the analysis of alienation performed by K. Marx considers only individual’s freedom in a class society but not class relations themselves.